Utilisation of district health information system and its associated factors among health professionals working at public health facilities of the southwest of Ethiopia: cross-sectional survey - Shuma Gosha Kanfe; Gebiso Roba Debele; Robera Demissie Berhanu; Habtamu Setegn Ngusie; Mohammedjud Hassen Ahmed (BMJ Open)
Objectives To assess utilisation of district health information system and its associated factors among health professionals in the southwest of Ethiopia, 2020.Setting Public health facilities in the southwest of Ethiopia.Participants A facility-based cross-sectional study was conducted among a sample of 260 participants.Main outcome measures The main outcome measure was utilisation of the district health information system.Results Overall, 149 (57.3%) of study participants had good utilisation of district health information systems (95% CI 50 to 64.2). Sufficient skills (Adjusted Odds Ratio (AOR) 3.83, 95% CI 1.92 to 7.64), being trained (AOR 3.90, 95% CI 1.95 to 7.79), high motivation (AOR 3.93, 95% CI 1.99 to 7.76), feedback provided (AOR 2.93, 95% CI 1.53 to 5.77) and regular supervision (AOR 3.06, 95% CI 1.56 to 6.01) were associated with utilisation of district health information systems.Conclusions In general, more than half of the respondents had good utilisation of district health information systems. Providing regular supportive supervision and feedback, having good skills on district health information system use, high motivation and being trained on district health information system will help to bring good utilisation of district health information system for decision making.